Bovine Colostrum Supplementation in Rabbit Diet Modulates Gene Expression of Cytokines, Gut–Vascular Barrier, and Red-Ox-Related Molecules in the Gut Wall - Federica Riva; Susanna Draghi; Alessia Inglesi; Joel Filipe; Paola Cremonesi; Antonio Lavazza; Patrizia Cavadini; Daniele Vigo; Stella Agradi; Laura Menchetti; Alessia Di Giancamillo; Lucia Aidos; et al. (Animals, 2024)
Rabbits, pivotal in the EU as livestock, pets, and experimental animals, face bacterial infection challenges, prompting a quest for alternatives to curb antibiotic resistance. Bovine colostrum (BC), rich in immunoregulatory compounds, antimicrobial peptides, and growth factors, is explored for disease treatment and prevention. This study assesses BC diet supplementation effects on rabbit intestines, examining gene expression. Thirty female New Zealand White rabbits at weaning (35 days) were divided into three experimental groups: control (commercial feed), 2.5% BC, and 5% BC. The diets were administered until slaughtering (81 days). BC-upregulated genes in the jejunum included IL-8, TGF-β, and CTNN-β1 at 5% BC, while PLVAP at 2.5% BC. Antioxidant-related genes (SOD1, GSR) were downregulated in the cecum and colon with 2.5% BC. BC 5% promoted IL-8 in the jejunum, fostering inflammation and immune cell migration. It also induced genes regulating inflammatory responses (TGF-β) and gastrointestinal permeability (CTNN-β1). BC 5% enhanced antioxidant activity in the cecum and colon, but no significant impact on anti-myxo antibody production was observed. These results suggest that BC has significant effects on the rabbit gastrointestinal tract’s inflammatory and antioxidant response, but further research is required to fully understand its histological and physiological impact.